2007
DOI: 10.1007/s00425-006-0453-3
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of NbBTF3 results in developmental defects and disturbed gene expression in chloroplasts and mitochondria of higher plants

Abstract: BTF3 (betaNAC) was originally isolated as a general transcription factor required for RNA polymerase II-dependent transcription, and later found to be a beta-subunit of nascent-polypeptide-associated complex that has been implicated in regulating protein localization during translation. In this study, virus-induced gene silencing of NbBTF3 encoding a Nicotiana benthamiana homolog of human BTF3 caused leaf yellowing and abnormal leaf morphology without altering the overall growth of the plant. The NbBTF3 gene i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 44 publications
2
24
0
1
Order By: Relevance
“…These results are similar to some other studies demonstrating that BTF3 take part in cell cycle regulation via interaction with cyclins [25]. Mutants lacking NAC also showed visible growth and morphological problem in yeast and tobacco [20, 26]. Furthermore, the inhibition of BTF3 participated in the repression of transcription and protein synthesis in apoptotic K562 cells [27], while change in BTF3 expression is linked with apoptosis in BL60 Burkitt lymphoma cells [28].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are similar to some other studies demonstrating that BTF3 take part in cell cycle regulation via interaction with cyclins [25]. Mutants lacking NAC also showed visible growth and morphological problem in yeast and tobacco [20, 26]. Furthermore, the inhibition of BTF3 participated in the repression of transcription and protein synthesis in apoptotic K562 cells [27], while change in BTF3 expression is linked with apoptosis in BL60 Burkitt lymphoma cells [28].…”
Section: Discussionsupporting
confidence: 87%
“…In Osj10gBTF3 Ri seedling, the expression level significantly decreased in root and shoot with increasing ABA concentration (Figure 6). Wang et al [6] observed a 62% increase in Osj10gBTF3 expression level with ABA, compared to a 22% reduction with GA 3 after treatment with the same concentration for 12 h. In previous reports, it has been observed that the transcript level of NbBTF3 remained unaffected when exposed to 100  ÎŒ M of ABA and GA 3 [26]. Similarly, He et al [29] did not find any significant change in SmBTF3, when treated with ABA for 24 hrs.…”
Section: Discussionmentioning
confidence: 96%
“…The sugarcane Nap is homologous to bNAP or BTF3. Silencing of NbBTF3 (bNAP) expression in Nicotiana benthamiana reduced chloroplast sizes and chlorophyll contents and the cells produced excessive amounts of ROS (Yang et al 2007). Sugarcane NAP could be regarded as a factor controlling homeostasis in chloroplasts, mitochondria and possibly the endoplasmic reticulum.…”
Section: Rust Infection-induced Metabolic Changesmentioning
confidence: 99%
“…In higher plants, transcription factor BTF3 is required for RNA polymerase II-dependent transcription. The downregulation of BTF3 expression reduces the chloroplast size and the chlorophyll content [46]. Therefore, the upregulation of BTF3 activity may contribute to chloroplast development in Chlorella to accommodate light stress.…”
Section: Discussionmentioning
confidence: 99%